Psychological aspects of educational socialization of children with autism spectrum disorders in the context of current challenges - ZAKHOZHA, Iryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background The socialization of children with autism in war conditions presents a special challenge that requires an attentive and sensitive approach. Military conflicts can create additional stress and trauma for both children with autism and families. During times of war, ensuring safety and stability for children is especially important, and for children with autism, predictability of the environment is important, so it is necessary to create a stable and predictable surrounding. The purpose of the article is a theoretical analysis of the problem of socialization and difficulties of adaptation of children with ASD in preschool and primary school educational institutions in war conditions. The purpose of the article: to analyze the problems of socialization and adaptation difficulties of children with ASD. Methods: analysis, generalization, systematization. Results. The socialization of children with ASD in a preschool educational institution includes the following difficulties. Children with autism may have limited verbal and nonverbal communication skills, making it difficult to interact with other children. It is important to provide additional opportunities to teach communication skills through game scenarios, simulations and special programs. The socialization of children with autism spectrum disorders into the school environment may face a number of unique challenges due to changing environments and increased social expectations. Children with ASD may have difficulty establishing and maintaining social connections. Children have limited or unusual interests, which may make it difficult to include them in general school activities. It is important to create opportunities for individual and group activities that meet the interests of the child with ASD. Conclusions. 1. The socialization of children with ASD in a preschool educational institution experiences the following difficulties: limited verbal and nonverbal communication skills; sensitivity to sounds and lighting; stereotypical behavior; problems recognizing the emotions of others and expressing your own. 2. The socialization of children with autism spectrum disorders in the school environment may face a number of special challenges, namely: limited interests; difficulty understanding social norms and expectations; lack of independence; undeveloped self-care skills; attention deficit; low level of concentration.